USE AND OCCUPATION OF THE APPROPRIATE SOIL FOR ENDS OF CONSERVATIONIST PLANNING OF WATERSHED OF THE STREAM SAO CAETANO - BOTUCATU(SP) - Campos, Sergio [UNESP]; Millani, Thais Maria [UNESP]; Silveira, Gabriel Rondina Pupo da [UNESP]; Pissarra, Teresa Cristina Tarle [UNESP]; Garcia, Yara Manfrin [UNESP]; Campos, Mariana de [UNESP]; Polonio, Vanessa Durante [UNESP]; Felipe, Andrea Cardador [UNESP]; Silva, Clescy Oliveira da [UNESP]; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; et al. (Fundacion General Univ Politecnica Madrid, 2014)
This research had as main objective to study the better land use of the Sao Caetano Stream Watershed - Botucatu(SP) in soil and slope mapping, as well as the decision making according to the Land Use Capability map, by using a Geographical Information System IDRISI - Selva . The study area is located between the coordinates: 48 degrees 26 ' 25 '' W, 48 degrees 29 ' 27 '' W, 22 degrees 52 ' 32 '' S, in an area of 3316.95ha. The land use capabilitymap of the watershed was obtained from slope and soil cross mapping,using the table of the capability classes of the land uses and the recommendations of the Brazilizn Land Capability Classes from the survey of the physical environment and the capability to land use systems. The IIIs , and IVs ans Vie subclasses was presented in more than 70 % of the area and almost 100% of the units of soils was a Typic Oxisoil and Neosol. The capability classes III and IV , divided into subclasses IIIs ; IIIs , and ; IVe ; IVs occupied 77.56% of the total area of the watershed, showing the great potential for annual crops, perennial pastures and or reforestation according to their capability to use. The IDRISI GIS - enabled by its modules the discrimination of the land uses capabilities, the better land use mapping and the quantification of the areas of the subclasses capabilities to land use of the watershed.
Keywords: geoprocessing; soil units; deelivity